IMMU-12. T-CELL THERAPIES DEMONSTRATE EFFICACY WITHOUT TOXICITY IN IMMUNOCOMPETENT MODELS OF BRAINSTEM TUMORS. Issue 2 (22nd June 2018) - Schuelke, Matt; Evgin, Laura; Wongthida, Phonphimon; Thompson, Jill; Kottke, Tim; Sanchez-Perez, Luis; Sampson, John; Vile, Richard
Abstract: Diffuse intrinsic pontine glioma (DIPG) is a pediatric brainstem tumor with a dismal prognosis and no curative treatments. Immunotherapy has been considered as a treatment for these tumors because of its ability to provide specific and sustained tumor killing. By nature, this approach is inflammatory and remains controversial due to the potential for catastrophic inflammatory toxicity in the brainstem. In order to address whether this approach should be considered as a clinical option, we characterized the efficacy/toxicity profile of transgenic and chimeric antigen receptor (CAR) T-cell therapies in the brainstem using immunocompetent, syngeneic mouse models. We first adoptively transferred naïve transgenic T-cells recognizing the model tumor antigens gp100 or ovalbumin to treat established aggressive, transplantable murine tumors in the brainstem. Encouragingly, this therapy significantly extended median survival (16 to 32 days; p<.001) with no signs of therapeutic toxicity. We plan to expand these studies by incorporating hgp100 into a spontaneously-occurring, engineered model of DIPG, followed by transgenic T-cell treatment. Lastly and most clinically-relevant, we have used CAR T-cell therapy to treat B16 melanoma engineered to express EGFRvIII and implanted into the brainstem. This therapy extended median survival from 14 to 30 days (p<.001). We plan to evaluate whether combinatorial approaches using checkpoint inhibitors or oncolytic viruses can further enhance survival. Together these data from immunocompetent mouse models demonstrate that T-cell immunotherapies are well- tolerated and efficacious against tumors located in the brainstem, opening the door for future clinical trials.